2016
DOI: 10.1026/0012-1924/a000150
|View full text |Cite
|
Sign up to set email alerts
|

mini-q: Intelligenzscreening in drei Minuten

Abstract: Zusammenfassung.  1968 stellte Baddeley ein ebenso schlichtes wie ökonomisches Instrument zur Erfassung von verbalem reasoning bzw. des logischen Schlussfolgerns auf Grundlage grammatikalischer Transformationen vor, welches eine Fähigkeitseinschätzung in nur 3 Minuten erlaubt ( Baddeley, 1968 ). Aufgrund grammatikalischer Besonderheiten der englischen Sprache ließ sich dieser bis heute angewandte Test (z. B. Chamorro-Premuzic & Furnham, 2008 ) jedoch nicht direkt übertragen. Wir stellen in diesem Artikel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…This suggests that there was a potential lack of motivation among at least some participants. However, in a recent study, Baudson and Preckel (2015) found that in other rather simple cognitive tasks, the proportion of successful participants was also only INDIRECT QUESTIONS: COMPREHENSIBILITY AND PRIVACY 27 90%, and thus, close to the accuracy we observed in the DQ condition. This provides evidence for the notion that it is probably unrealistic to expect perfect scores in tasks like the ones we investigated.…”
Section: Limitations and Future Directionsmentioning
confidence: 85%
“…This suggests that there was a potential lack of motivation among at least some participants. However, in a recent study, Baudson and Preckel (2015) found that in other rather simple cognitive tasks, the proportion of successful participants was also only INDIRECT QUESTIONS: COMPREHENSIBILITY AND PRIVACY 27 90%, and thus, close to the accuracy we observed in the DQ condition. This provides evidence for the notion that it is probably unrealistic to expect perfect scores in tasks like the ones we investigated.…”
Section: Limitations and Future Directionsmentioning
confidence: 85%
“…We used a screening measure of fluid intelligence, the mini-q (Baudson and Preckel 2016), to have an additional indication of the groups' giftedness over and above their identification as member of Mensa or recipient of honors for outstanding success in education. In line with our expectation, members of Mensa showed the highest values in fluid intelligence, followed by the High Achievers.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid intelligence was assessed by the mini-q intelligence screening test (Baudson and Preckel 2016). The test presents 64 sentences, each followed by a figure (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The Mini-Q test of GMA ( Baudson and Preckel, 2015 ) did not predict whether participants found the win–win solution, suggesting that the task is not simply about cognitive abilities. Instead, detecting win–win solutions may require a certain mind-set and not general mental abilities (e.g., creative problem solving).…”
Section: Studymentioning
confidence: 97%
“…As a measure of mental ability, participants completed the Mini-Q ( Baudson and Preckel, 2015 ), a 3-min intelligence screening test based on a verbal reasoning test developed by Baddeley (1968) . On this test, participants are asked to decide as quickly as possible if a statement correctly describes a constellation of three (geometrical) figures by clicking a right or a wrong button next to the statement.…”
Section: Studymentioning
confidence: 99%